Hamāre Śrī Golavalakarajī kī puṇya smrtiyām - Prabhudatta, Brahmachari (Saṅkīrtana Bhavana, 1973)
Reminiscences about Madhav Sadashiv Golwalkar, 1906-1973, former chief of the Rashtriya Swayam Sewak Sangh.